Experimental study on the homogeneity of microbial grouting to reinforce calcareous sand - Xiaoyan Ding; Ping Li; Xiaoyong Mao; Xinlei Zhang (PLoS ONE, 2025)
Microbial-induced calcium carbonate precipitation (MICP) technology has shown remarkable potential in environmental engineering fields, such as soil improvement, pollution control and hydrological barrier construction. However, when applied to the reinforcement of sandy materials, the main challenge of MICP technology is the nonuniformity of the curing effect, which greatly restricts the application of this technology in practical engineering. The aim of this study is to explore and optimise the application of MICP technology in calcareous sand reinforcement to improve the uniformity and efficiency of the reinforcement. By treating calcareous sand samples from an island in the South China Sea with Pasteurella spp. octococcus and conducting 75 unconfined compressive tests, the effects of different filling rates (0.5, 3, and 7 mL/min), cementing solution concentrations (0.25, 0.5, 1, and 3 mol/L), and numbers of filling rounds (2, 4, 6, and 8 rounds) on the homogeneity of the reinforcement were systematically investigated. The best curing effect was achieved at an infusion rate of 3 mL/min, which improved the strength of the soil while maintaining a high degree of uniformity. A good balance between compressive strength and uniformity was achieved at cement concentrations ranging from 0.5 mol/L to 1 mol/L. Increased grouting effectively improved the distribution uniformity of the MICP cemented structure. The destructive strain εf of the cured specimens ranged from 1.5% to 6%, which was inversely proportional to the peak strength qu; the elastic modulus E50 was positively correlated with qu. The stress‒strain curves were characterised by three phases of slow increase, rapid increase and sudden decrease in stress under different binder concentration conditions. For the unevenly cured samples, the stress‒strain curves were disordered, and there were multiple stages of stress peaks. This work confirmed that the MICP technique can significantly enhance the mechanical properties of calcareous sand, but precise control of the filling parameters is needed to ensure the uniformity and efficiency of the reinforcement. The suggested optimised parameters are as follows: a filling rate of 3 mL/min, a cementitious solution concentration of 0.5 mol/L to 1 mol/L, and a reasonable number of filling. This study provides a theoretical basis and practical guidance for the application of MICP technology in calcareous sand reinforcement scenarios.